To help deaf children go to school, help their parents | Blog | Global Partnership for Education - KIX, GPE (2019)
25 years after the Salamanca Statement, there are still too many child ren with disabilities who don’t go to school. One way to effectively r emove a barrier to their schooling is through the transformative power of parents groups.